Analysis of Vaccine efficacy during the COVID-19 pandemic period using CSF-ELECTRE-I approach. (2022) - Narayanamoorthy, Samayan; Pragathi, Subramaniam; Shutaywi, Meshal; Ahmadian, Ali; Kang, Daekook
Abstract: COVID-19 vaccinations have been shown to be safe, efficacious, and life-saving. They, like other vaccines, do not entirely protect everyone who receives them, and no one knows how effectively they can prevent people from spreading the virus to others or whether the booster dosage is dangerous to some vulnerable people. So, in addition to getting vaccinated, we must continue with additional efforts to combat the pandemic. Quantitatively, the pragmatic, appropriate, and phenomenal mechanism of the complex spherical fuzzy set enhances the decision-making efficacy and the ordering quality of the ELECTRE I method to include a profitable and optimal approach for MAGDM. In the CSF environment, critically ill patients are investigated systematically using a pairwise comparison based ELECTRE-I technique. In this paper, we improve the precision of the CSF-based ELECTRE-I approach to an unique score function. The suggested approach's comparability is examined with techniques that should provide equal importance to the alternatives, and the presented score function's reliability is validated using the existing score function with the two cases. Highlights: Vaccine efficacy is analyzed for vulnerable groups. In the CSF environment, preventive factors are discussed. To outrank the alternatives, the ELECTRE-I approach is employed. To achieve the desirable outcomes, a score function is compared by Akram's Score function.